Assistance in Enhancing the Functional Value of the Yellow Tofu Production System through a Value Engineering Approach at UD SDD Kediri - Yuniati, Yuyun; Mohamad, Silvana; Fais, Moh. Ainul (Journal of Community Practice and Social Welfare, 2026)
Micro-scale tofu industries often operate using conventional production systems that evolve through habit rather than structured technical planning, leading to inefficiencies in energy use and workflow organization. This Community Service program was conducted at UD SDD Kediri to enhance the functional value of its yellow tofu production system through a value engineering approach. The activity focused on improving the combustion system and facility layout without requiring costly technological replacement. The methodology consisted of situational analysis, functional identification, process mapping, simulation of layout improvement, limited implementation, and evaluation. Initial observations showed a production cycle time of approximately 180 minutes per batch, material movement distance of ±22 meters, and high heat exposure due to an uninsulated traditional furnace. Layout simulation reduced movement distance to ±14 meters and shortened movement time from 25 to 15 minutes, indicating a potential efficiency improvement of around 36% in motion-related activities. Minor adjustments in airflow and heat direction improved combustion stability and reduced direct heat exposure. The findings demonstrate that inefficiencies were primarily associated with weak supporting functions rather than production capacity limitations. The program strengthened both technical configuration and managerial awareness of function–cost relationships, confirming that incremental value engineering interventions provide a feasible pathway for efficiency enhancement in micro-scale food enterprises.